The Influence of Motivation and Work Discipline on Teacher Performance at Yos Sudarso Dobo Junior High School - Christina N.Sihombing; Rutman Lumbantoruan; Ivakdalam , Veronika Ingrit (Universitas Kristen Indonesia, 2022)
The objectives of this study are: To identify the influence of motivation on teacher performance at Yos Sudarso Dobo Junior High School and to identify the influence of Work Discipline on Teacher Performance at Yos Sudarso Dobo Junior High School. This research includes the type of associative research. The research location is Yos Sudarso Dobo Junior High School which is located at Mutiara street Number .132. Aru Islands District. Maluku Province. The research method used in this study was a questionnaire and used 26 respondents as the population and sample. to calculate each indicator, using a Likert scale and the data in this study used qualitative data obtained from the questionnaire which was converted into quantitative data to convert qualitative data to quantitative data using the Succesive Interval (MSI) Method. Through the MSI method, the results of the ordinal data questionnaire were transformed into interval data, while to test the research instrument using data analysis techniques, the Validity and Reliability Test of the questionnaire. Furthermore, simple linear regression analysis is used to find the regression equation. Next, do the coefficient of determination test to determine the effect between the independent variable and the dependent variable. And to test the hypothesis using t test (partial). The results showed that in testing the hypothesis using the t-test partially Motivation has a significance value of 0.000 > 0.05, meaning that there is a significant influence between motivation on teacher performance and work discipline has a significance value of 0.000 <0.05, meaning that there is a significant influence between work discipline on teacher performance.Keywords: Motivation, Work Discipline, Teacher Performance